Paradigma Keadilan Restoratif Dalam Putusan Hakim - Hariyanto, Diah Ratna Sari; Pradnya Yustiawan, Dewa Gede (Kertha Patrika; Vol 42 No 2 (2020), 2020)
Discriminatory treatments of judge s have dominated the report s to the Judicial Commission. Injustice, in fact, is one of the lowest value attitudes of judges according to Judicial Commission assessment results. Indeed, showing justice is not easy for judges but to date in its development appears restorative justice that provides justice for all parties. Its future existence and response are interesting to be criticized. Based on this, the purpose of this study is to examine the paradigm of restorative justice in making legal decisions of judges on legal cases and the construction of the judges’ decisions which are paradigmatic in Restorative Justice. This research uses normative legal research with four types of approaches, which are case approach, legislative approach, conceptual approach, historical approach, and comparative approach. The results of the study show the restorative justice paradigm prioritizing restoration or amelioration will seek to provide justice, certainty and usefulness of the law, as well as realize progressive and responsive laws, and this makes it appropriate to be used as a judge’s paradigm in deciding a case. In constructing restorative justice-based judges’ decisions, judges do only make decisions based on the Criminal Procedure Code (KUHAP), but substantially, through the restorative justice paradigm the judges will consider justice for all parties (victims, perpetrators of crime, and the public). Judges do not make decisions based on retributive or retaliation goals but hold on to the values, concepts, principles, and basics of restorative justice prioritizing restoration or amelioration of the parties, meeting the needs of the parties, and prioritizing expediency.   Discriminatory treatments of judges have dominated the reports to the Judicial Commission. Injustice, in fact, is one of the lowest value attitudes of judges according to Judicial Commission assessment results. Indeed, showing justice is not easy for judges but to date in its development appears restorative justice that provides justice for all parties. Its future existence and response are interesting to be criticized. Based on this, the purpose of this study is to examine the paradigm of restorative justice in making legal decisions of judges on legal cases and the construction of the judges’ decisions which are paradigmatic in Restorative Justice. This research uses normative legal research with four types of approaches, which are case approach, legislative approach, conceptual approach, historical approach, and comparative approach. The results of the study show the restorative justice paradigm prioritizing restoration or amelioration will seek to provide justice, certainty and usefulness of the law, as well as realize progressive and responsive laws, and this makes it appropriate to be used as a judge’s paradigm in deciding a case. In constructing restorative justice-based judges’ decisions, judges do only make decisions based on the Criminal Procedure Code (KUHAP), but substantially, through the restorative justice paradigm the judges will consider justice for all parties (victims, perpetrators of crime, and the public). Judges do not make decisions based on retributive or retaliation goals but hold on to the values, concepts, principles, and basics of restorative justice prioritizing restoration or amelioration of the parties, meeting the needs of the parties, and prioritizing expediency.